Domino : caught in the crisis - Ma, Eve A.; Malena, Antonio de la; Palomino Productions ([Berkeley, California] : Palomino Productions, 2014)
Luis, an ordinary individual in Spain caught up in that country's economic crisis, a crisis that began in the United States. As we watch him struggle with unemployment and the threat of foreclosure, we are reminded of the 4 million long-term unemployed in the U.S., the growing gap between rich and poor, and the millions of foreclosures that have occurred since 2008. Luis does all the right things: goes to an unemployment office, checks out the employment listings posted by private firms, checks the newspaper listings, asks friends for a job, accepts whatever part-time work is offered to him...and goes to the bank to apply for a loan--
Originally released as a motion picture in 2014
Antonio de la Malena, Luis de la Tota, Nicola s Montoya, Javier Padilla, Salvador Valle, Esteban Vian~a.
Cinematographer and editor, Eve A. Ma ; music, Antonio de la Malena, Malena Hijo.
In Spanish with English subtitles. Also available without the subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed July 2, 2018)
Keywords: Unemployed -- Spain -- Drama; Older unemployed -- Spain -- Drama; 15-M (Organization) -- Drama; Financial crises -- Spain -- 21st century -- Drama; Spain -- Economic conditions -- 21st century -- Drama; Jerez de la Frontera (Spain); Feature films; Internet videos; Streaming video